2005
DOI: 10.1002/ajh.20263
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian multicenter retrospective study evaluating transjugular liver biopsy in patients with congenital bleeding disorders and hepatitis C: Is it safe and useful?

Abstract: Prior to the introduction of virally inactivated clotting factor concentrates, the majority of individuals with congenital bleeding disorders became infected with the hepatitis C virus. Although liver biopsy is valuable in prognosis and guiding antiviral therapy, there is a reluctance to perform biopsies in this population because of the risk of hemorrhage. The purpose of this study was to evaluate the safety of transjugular liver biopsy, and the usefulness of evaluating liver histology in this patient populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 42 publications
1
51
0
6
Order By: Relevance
“…However, critical review of the existing literature suggests that the risk of bleeding (presumably due to capsular hemorrhage) appears to be approximately similar to that associated with standard percutaneous biopsy, 35,105,114,159,180 perhaps related to the risk of capsular piercing with subsequent hemorrhage. In a recent systematic review, minor and major complications were reported in 6.5% and 0.6%, respectively, of 7649 patients after transvenous biopsy.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, critical review of the existing literature suggests that the risk of bleeding (presumably due to capsular hemorrhage) appears to be approximately similar to that associated with standard percutaneous biopsy, 35,105,114,159,180 perhaps related to the risk of capsular piercing with subsequent hemorrhage. In a recent systematic review, minor and major complications were reported in 6.5% and 0.6%, respectively, of 7649 patients after transvenous biopsy.…”
Section: Complicationsmentioning
confidence: 99%
“…These include patients with factor VIII (FVIII) or IX (FIX) deficiency, von Willebrand's disease and other hereditary bleeding disorders, [156][157][158][159] and those with sickle cell anemia. 160 Patients with known underlying coagulopathy requiring liver biopsy represent a challenge, but it should be emphasized that liver biopsy (percutaneous or transvenous) can be performed in these patients (with definitive factor replacement).…”
Section: Contraindicationsmentioning
confidence: 99%
“…Liver biopsy is considered to be very useful in diagnosing and treating patients with abnormal liver function tests [1][2][3][4]. Transjugular biopsy allows histological samples to be acquired from patients in whom percutaneous puncture is contraindicated [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Factor VIII or IX replacement to achieve levels 80 to 100 U/dL prior to biopsy, with continued factor replacement to maintain levels Ͼ50 U/dL for 2 to 4 d following biopsy, has been associated with a 1% to 2% rate of clinically significant bleeding. 21 Recently, transient elastography has been proposed as a noninvasive tool for the assessment of liver fibrosis in hemophilia patients. 22 Liver transplantation is an option for hemophilia patients with end-stage liver disease who are infected with HCV or HCV-/HIV and corrects the factor deficiency.…”
Section: Viral Diseasementioning
confidence: 99%